An Agricultural Perspective in Internet of Things - Mittal, M; Pandita, R; Kumari, D (International Journal of Computer Sciences and Engineering, 2025)
Internet of Things (IoT) is a pioneer to the field of wireless communication. IoT is that network in which things are interconnected wirelessly via smart sensors. Smart sensors are equipped with various sensing and monitoring parameters depending on the scenarios where they are actually deployed. IoT is such an upcoming thing in which there is no need of human interference. IoT has wide range of applications like in agriculture, automotive industries, transportation, hospitals etc. This paper has focussed on agricultural application based on wireless technology to generate an effective value such as enhancement of agriculture productivity, standard increment of agriculture products in the entire procedure of agriculture production. Conclusively, We get better quality of agricultural products.